Sterol profiling of Leishmania parasites using a new HPLC-tandem mass spectrometry-based method and antifungal azoles as chemical probes reveals a key intermediate sterol that supports a branched ergosterol biosynthetic pathway. (December 2022) - Feng, Mei; Jin, Yiru; Yang, Sihyung; Joachim, Arline M.; Ning, Yu; Mori-Quiroz, Luis M.; Fromm, Jacob; Perera, Chamani; Zhang, Kai; Werbovetz, Karl A.; Wang, Michael Zhuo
Abstract: Human leishmaniasis is an infectious disease caused by Leishmania protozoan parasites. Current chemotherapeutic options against the deadly disease have significant limitations. The ergosterol biosynthetic pathway has been identified as a drug target in Leishmania . However, remarkable differences in the efficacy of antifungal azoles that inhibit ergosterol biosynthesis have been reported for the treatment of leishmaniasis. To better understand the sterol biosynthetic pathway in Leishmania and elucidate the mechanism underlying the differential efficacy of antifungal azoles, we developed a new LC-MS/MS method to study sterol profiles in promastigotes of three Leishmania species, including two L. donovani, one L. major and one L. tarentolae strains. A combination of distinct precursor ion masses and LC retention times allowed for specific detection of sixteen intermediate sterols between lanosterol and ergosterol using the newly developed LC-MS/MS method. Although both posaconazole and fluconazole are known inhibitors of fungal lanosterol 14α-demethylase (CYP51), only posaconazole led to a substantial accumulation of lanosterol in azole-treated L. donovani promastigotes. Furthermore, a key intermediate sterol accumulated by 40- and 7-fold when these parasites were treated with posaconazole and fluconazole, respectively, which was determined as 4α, 14α-dimethylzymosterol by high resolution mass spectrometry and NMR spectroscopy. The identification of 4α, 14α-dimethylzymosterol supports a branched ergosterol biosynthetic pathway in Leishmania, where lanosterol C4- and C14-demethylation reactions occur in parallel rather than sequentially. Our results suggest that selective inhibition of leishmanial CYP51 is insufficient to effectively prevent parasite growth and dual inhibitors of both CYP51 and the unknown sterol C4-demethylase may be required for optimal antiparasitic effect. Graphical abstract: Image 1 Highlights: Remarkable differences in the efficacy of antifungal azoles have been reported for the treatment of leishmaniasis. A new LC-MS/MS method has been developed to study sterol profiles in promastigotes of three Leishmania species. A key intermediate sterol was determined as 4α, 14α-dimethylzymosterol by mass spectrometry and NMR spectroscopy. The identification of 4α, 14α-dimethylzymosterol supports a branched ergosterol biosynthetic pathway in Leishmania . Dual inhibition of both CYP51 and the unknown sterol C4-demethylase may be required for optimal antileishmanial effect.